TRANSFORMATIONAL LEADERSHIP IN ORGANIZATIONAL TRANSFORMATION - Maisyura Maisyura; Ti Aisyah; Rico Nur Ilham (Jurnal Ekonomi, 2022)
This article discusses the importance of the role of leadership in dealing with organizational change. Of the various leadership styles, the author explores transformational leadership which is considered the most appropriate as the spearhead of organizational transformation. Using the literacy study method sourced from books and writings in scientific journals which are then compiled with the author's point of view, this paper tries to explore the role of leadership in leading organizational change with all the characteristics possessed by this leadership style. This paper presents organizational transformation by looking at the important role of leadership as a driving force for change in the organizational transformation process, both its charismatic role and its instrumental role. Transformational leadership is considered the most suitable to be applied to make organizational change to be able to synergize with unexpected environmental changes and can occur at any time without being predictable, Transformative leaders have the knowledge, expertise, and skills and dare to act and take risks with the power of a visionary and full of vision. calculations and have a strategy to produce innovations for the success of a transformation. with eight stages of Kotter's change known as Kotter's 8 Steps Changes Model which is carried out using the concept of organizational transformation proposed by Gouillert and Kelly known as the 4R (Reframing, Restructure, Revitalization and Renewal).